IMPLEMENTASI ASESMEN DIAGNOSTIK NON KOGNITIF SISWA KELAS III SD NEGERI GAYAMSARI 02 KOTA SEMARANG - Sayyidatul Hasna; Mira Azizah; Espiyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to analyze how the implementation of non-cognitive diagnostic assessments for class IIIA students at SDN Gayamsari 02 Semarang City. This research uses descriptive analytical method with a qualitative approach. Data collection techniques used are through observation, questionnaires and interviews. The research subjects were students in class III A Gayamsari 02 with a total of 25 students. While data analysis is done through data reduction, data presentation and drawing conclusions. The results of the planning analysis obtained data that class IIIA students at SDN Gayamsari 02 had sufficient development or needed to be improved as evidenced by 16% of students' emotional development was very good, .48% of students' emotional development was good and 36% of students' emotional development was sufficient or needed to be improved. Students' motivation to learn is very good, as evidenced by 52% of students having very good learning motivation, .32% of students having good learning motivation and 16 students having sufficient learning motivation or needing improvement. While the learning styles of students tend to vary, namely 8 students have an auditory learning style, 10 students have a visual learning style, and 7 students have a kinesthetic learning style.